Leucine‐rich repeat containing protein LRRC8A is essential for swelling‐activated Cl− currents and embryonic development in zebrafish. Issue 19 (28th September 2016) - Yamada, Toshiki; Wondergem, Robert; Morrison, Rebecca; Yin, Viravuth P.; Strange, Kevin
Abstract: A volume‐regulated anion channel (VRAC) has been electrophysiologically characterized in innumerable mammalian cell types. VRAC is activated by cell swelling and mediates the volume regulatory efflux of Cl − and small organic solutes from cells. Two groups recently identified the mammalian leucine‐rich repeat containing protein LRRC8A as an essential VRAC component. LRRC8A must be coexpressed with at least one of the other four members of this gene family, LRRC8B‐E, to reconstitute VRAC activity in LRRC8 −/− cells. LRRC8 genes likely arose with the origin of chordates. We identified LRRC8A and LRRC8C‐E orthologs in the zebrafish genome and demonstrate that zebrafish embryo cells and differentiated adult cell types express a swelling‐activated Cl − current indistinguishable from mammalian VRAC currents. Embryo cell VRAC currents are virtually eliminated by morpholino knockdown of the zebrafish LRRC8A ortholog lrrc8aa . VRAC activity is fully reconstituted in LRRC8 −/− human cells by coexpression of zebrafish lrrc8aa and human LRRC8C cDNAs. lrrc8aa expression varies during zebrafish embryogenesis and lrrc8aa knockdown causes pericardial edema and defects in trunk elongation and somatogenesis. Our studies provide confirmation of the importance of LRRC8A in VRAC activity and establish the zebrafish as a model system for characterizing the molecular regulation and physiological roles of VRAC and LRRC8 proteins. Abstract : A volume‐regulated anion channel (VRAC) has been electrophysiologically characterized in innumerable mammalian cell types. Recent studies have identified the mammalian leucine‐rich repeat containing protein LRRC8A as an essential VRAC component. Our studies provide confirmation of the importance of LRRC8A in VRAC activity and establish the zebrafish as a model system for characterizing the molecular regulation and physiological roles of VRAC and LRRC8 proteins.